2010
DOI: 10.1016/j.devcel.2010.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Pitchfork Regulates Primary Cilia Disassembly and Left-Right Asymmetry

Abstract: SUMMARY A variety of developmental disorders have been associated with ciliary defects, yet the controls that govern cilia disassembly are largely unknown. Here we report a mouse embryonic node gene, which we named Pitchfork (Pifo). Pifo associates with ciliary targeting complexes and accumulates at the basal body during cilia disassembly. Haploinsufficiency causes a unique node cilia duplication phenotype, left-right asymmetry defects, and heart failure. This phenotype is likely relevant in humans, because we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
140
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(146 citation statements)
references
References 48 publications
1
140
0
4
Order By: Relevance
“…23,24 Remarkably, these cells retained cilia during mitosis. 24 Similar cellular phenotypes were seen when Aurora A kinase activity was inhibited by overexpression of a pathogenic mutant of Pifo, R80K. 24 Mice or humans heterozygous for mutations in Pifo were shown to have laterality defects, possibly due to structural defects of the cilia in the embryonic node, 24 suggesting that the pool of Pifo at the basal body during the initial course of cilia resorption may account for proper left-right patterning.…”
Section: Cilia and The Cell Cyclementioning
confidence: 99%
See 4 more Smart Citations
“…23,24 Remarkably, these cells retained cilia during mitosis. 24 Similar cellular phenotypes were seen when Aurora A kinase activity was inhibited by overexpression of a pathogenic mutant of Pifo, R80K. 24 Mice or humans heterozygous for mutations in Pifo were shown to have laterality defects, possibly due to structural defects of the cilia in the embryonic node, 24 suggesting that the pool of Pifo at the basal body during the initial course of cilia resorption may account for proper left-right patterning.…”
Section: Cilia and The Cell Cyclementioning
confidence: 99%
“…Kinzel and colleagues showed that Pifo accumulates at the basal body during the early stages of cilia disassembly and participates in the ciliary resorption process working along with Aurora A. 24 The authors reported defects in ciliary disassembly, centriole overduplication and multipolar spindle formation in cells lacking one allele of Pifo. 23,24 Remarkably, these cells retained cilia during mitosis.…”
Section: Cilia and The Cell Cyclementioning
confidence: 99%
See 3 more Smart Citations